PEMBERDAYAAN PEREMPUAN DI KAWASAN KUTA SEBAGAI UPAYA PENINGKATAN KUALITAS PARIWISATA BALI - Suar dana, I Wayan (PIRAMIDA; Vol. 6, No.2 Desember 2010, 2012)
According to convention, tourism sector is public sector, that is aman area, but a women area is domestic sector. Based on tourismdevelopment in Bali, there are many jobs opportunity that can beentered by woman community. This research investigates theinvolvement of women in tourism object in Kuta region as analternative for improving their social, cultural and economic statusand roles in societies. Findings indicate that women have beeninvolved, to a certain extent, in Kuta region. There were twodifferent groups of women who were involved i.e. high stratumand mid and lower stratum. The formmer was actively involvedin any kinds of activities including decision making as they werethe owners of the attractions. The latter, although has beeninvolved, was pasive. The respondents mostly consider thatbeing involved in tourism destinations means that they have morepower in society and family. They believed that economicallythey were advantageous as they can contribute to the running ofthe family budget. Culturally, it was believed that by beinginvolved they had more reponsibility in preserving local culture oridentity.
Keywords: empowerment, women, tourism